Newfoundland and Labrador gambling prevalence study 2005 [Canada] - O'Keefe, Carolyne; Legg, Heather (Borealis, 2014)
This study is the first to address gambling issues specific to the province and provides current baseline information regarding the prevalence of gambling and problem gambling in Newfoundland and Labrador (NL). The objectives of this study included measuring: 1) the prevalence of gambling and problem gambling in the province, 2) profiles of gambler sub-types and players of certain gambling activities, 3) the relationship between gambling and correlates of gambling including substance use and mental health, 4) consequences related to gambling and 5) awareness of support and treatment services. This is the CPGI baseline study of the prevalence of gambling and problem gambling in Newfoundland and Labrador (N=2,596).